The level of information and communication technology use by museums in Malaysia - Abu Bakar, Juliana Aida; Jahn Kassim, Puteri Shireen; Mahmud, Murni (2010)
The recent advances in information and communication technology (ICT)have tremendously affected the way teaching and learning (T&L) is delivered in both formal and informal education. For formal education, Malaysia is reaping the benefits of ICT through Smart School project under MSC Malaysia initiatives. For informal education, an initial observation suggest that museums, a critical institution which protects and preserves the national heritage as well as delivers the knowledge to the general public, employ less ICT in their exhibition halls. As there is lack of empirical evidence to prove the above, this study aims to determine the level of ICT use by museums in Malaysia and attempts to understand issues that have a profound influence on ICT implementation in their institution and hence in their exhibition halls. A survey was conducted among 22 governing institution for museums throughout Malaysia. The finding suggest that museums have adequate ICT infrastructure, service, and applications to run day-by-day administration and operations. However, there are rooms for improvement when it comes to museum exhibition halls. This study further reveals several issues that restricted these museums from using ICT as one of the means for historical, cultural, and heritage knowledge to be delivered to the general public and puts forward few recommendations to possibly curb these issues.